ANALYSIS OF NETWORK RATES ACCESSED TO CASH - Iip Dyah Kusumaningati (Department of Management - Institut Shanti Bhuana, 2024)
The research is aimed at identifying and analyzing the influence of payments on cash and cash equivalents in PT. BPJS. The type of research in this study uses quantitative analysis of descriptions. Jamsostek (Persero). These results indicate that the total assets tend to increase by 20 – 30%. Meanwhile, Loans as well as Cash and Cash equivalents tend to experience fluctuating increases and decreases. Though the loan is not very influential against cash and cash equivalents, the loan must be kept in mind because if the loan has been paid it will give a significant contribution to the availability of cash. From the results of this analysis it is known that the loan contributes 14.7% to Cash and Cash equivalents. Though it does not significantly affect Cash and Equivalent Cash, but the contribution of 14.7% is a sufficiently meaningful contribution for cash and equivalent available to PT. Jamsostek (Persero).